Marketing Strategies Effecting To Product Buying Behavior Of Chinese Tourists In Chinatown, Samphanthawong, Bangkok - Chiyachantana, Chirasak (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The objectives of this research were: 1) to study Chinese tourists’ opinion towards marketing strategies effecting to product buying behavior in Chinatown area, 2) to compare buying behavior of Chinese tourists in Chinatown area which classified by personal factor, and 3) to study marketing strategies effecting to product buying behavior of Chinese tourists in Chinatown area. Questionnaires were used to collect data from 400 samples and using multi-stage sampling method. The statistical analysis included percentage, mean, Standard Deviation, Independent t-test, One Way ANOVA, Pearson's Product Moment Correlation Analysis and Stepwise multiple analysis. The finding showed that: 1.The overall of marketing strategies were in high (Mean =4.09,S.D.=0.25) by focus of the presentation was the highest physical appearance. The study of decision making to buy products showed the most of them have been visited 2 times for the purpose of enjoyment, have a partner / lover traveling, the recognition of information from the internet and the cost per time was 2,001-5,000 Baht respectively. 2. The overall of decision behavior were not difference, except career at statistically significant level of .05. 3. The study result of marketing strategies effecting to product buying behavior of Chinese tourists found that the most important factor was product (b = 0.191) marketing promotion (b= 0.142), service process (b= 0.17) and physical characteristics ( b= 0.130). The equation has 11 percentage predictive power and can write the equation as follow: Y = 3.460**+ 0.191 X1 *+ 0.072 X2 + 0.091 X3 + 0.142 X4 **+ 0.012 X5 + 0.117 X6 **+ 0.130 X7** 4. The suggestion of this research should develop products standard and tourism services for international standard as well as support for basic Chinese communication, which will be very useful and can provide information to Chinese tourists when there are problems or questions. Article history : Received 20 December 2019 Revised 1 March 2020 Accepted 5 March 2020 SIMILARITY INDEX = 0.00 %